2012
DOI: 10.1063/1.3676618
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of critical current density in GdBa2Cu3O7−δ thin films with BaSnO3 addition

Abstract: Articles you may be interested inA close correlation between nanostructure formations and the thickness dependence of the critical current density in pure and BaSnO3-added GdBa2Cu3O7-δ films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Tran et al [23] found that the 0.2-μm-thick GdBCO film had the highest J c of 3.8 × 10 6 A/cm 2 and the J c value decreased to 4.2 × 10 5 A/cm 2 as the film thickness increased to 0.55 μm. From our results, the J c of the 1,450-nm-thick film can achieve as high as 2.0 × 10 6 A/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tran et al [23] found that the 0.2-μm-thick GdBCO film had the highest J c of 3.8 × 10 6 A/cm 2 and the J c value decreased to 4.2 × 10 5 A/cm 2 as the film thickness increased to 0.55 μm. From our results, the J c of the 1,450-nm-thick film can achieve as high as 2.0 × 10 6 A/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Using multilayer technology, Foltyn et al have achieved J c values of up to 4.0 × 10 6 A/cm 2 in the film with a thickness of 3.5 μm, at_75 K, self-field on metal substrates [9]. Tran et al have overcome the rapid decrease of J c value by BaSnO 3 addition in (Gd) BCO films [23]. Feldmann et al achieved a J c (75.6 K, self-field) of 5.2 × 10 6 A/cm 2 in a single-layer 2.0-μm-thick YBCO film with BaZrO 3 (BZO) and Y 2 O 3 additions [24].…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the J c of GdBCO, introducing impurities as artificial pinning centers (APCs) is known to be one of the most effective methods [3][4][5][6]. BaSnO 3 (BSO) was selected as a dopant material because our previous study had shown that BSO provides a J c improvement via the formation of a BSO nanostructure [6][7][8] In the application of superconductor, T c is one of the properties as much important as J c . Variation in T c is reported to be related to the change in local structure, which is nowadays considered a key point for understanding mechanism of superconductivity.…”
Section: Introductionmentioning
confidence: 99%